2011
DOI: 10.1515/ijdhd.2011.039
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese Parental Expectation on Child’s Future Scale

Abstract: Based on the data collected from 125 parents in Hong Kong, the psychometric properties of the original 23-item Chinese Parental Expectation on Child ' s Future Scale (CPECF) are examined in this paper. Results showed that the scale had good reliability (internal consistency and test-retest reliability) and convergent validity in the sample. After deletion of six items, a revised scale (Revised-CPECF) was further developed. The Revised Chinese Parental Expectation on Child ' s Future Scale (Revised-CPECF) showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A sample item is, “I expect my child to have good salary in the future.” The respondents are required to rate each item on a 6-point Likert-type scale ranging from 1 = Strongly disagree to 6 = Strongly agree . MECF showed good reliability and validity in previous studies (Leung & Shek, 2011b). Higher scores indicate higher parental expectations of children’s future.…”
Section: Instrumentssupporting
confidence: 55%
“…A sample item is, “I expect my child to have good salary in the future.” The respondents are required to rate each item on a 6-point Likert-type scale ranging from 1 = Strongly disagree to 6 = Strongly agree . MECF showed good reliability and validity in previous studies (Leung & Shek, 2011b). Higher scores indicate higher parental expectations of children’s future.…”
Section: Instrumentssupporting
confidence: 55%
“…A 17-item measure was assessed in a previous validation study that showed internal consistency, divergent validity, and factorial validity (J. T. Y Leung & Shek, 2011c). Participants were requested to rate the degree of agreement with each item on a 6-point Likert-type scale ranging from "Strongly agree" to "Strongly disagree."…”
Section: Parental Expectations Of Children's Future Scale (Pecf)mentioning
confidence: 99%
“…The scale was developed with 23 items measuring dimensions of parental expectations of children ' s future in terms of educational achievement, self-reliance, occupation, family obligation, and conduct. A revised PECF with 17 items was assessed in a previous validation study and both fathers ' (FECF) and mothers ' responses (MECF) of the measure showed internal consistency, divergent validity, and factorial validity [59] . Participants were requested to rate the degree of agreement with each item on a 6-point Likert scale ranging from " Strongly agree " to " Strongly disagree ".…”
Section: Parental Expectations Of Children ' S Future Scale (Pecf)mentioning
confidence: 99%